Author Correction to: Quantum chemical studies, vibrational analysis, molecular dynamics and docking calculations of some ent-kaurane diterpenes from Annona vepretorum: a theoretical approach to promising anti-tumor molecules - Costa, Renyer A.; da Silva, Jonathas Nunes [UNESP]; Oliveira, Kelson M. T.; Dutra, Lívia M.; Costa, Emmanoel V. (Springer Nature, 2020)
In the original published version of the article, some typos are in the text, being in disagreement with the information found in Tables 1, 2, 3 and 4 and in the section “Molecular dynamic studies”.
Author Correction to: Quantum chemical studies, vibrational analysis, molecular dynamics and docking calculations of some ent-kaurane diterpenes from Annona vepretorum: a theoretical approach to promising anti-tumor molecules (Structural Chemistry, (2020), 31, 3, (1223-1243), 10.1007/s11224-020-01491-2)